Reversing the cumulative redundancy bias to demonstrate metacognitive flexibility in cue utilization - Grüning, David; Alves, Hans; Mata, André; Fiedler, Klaus (Journal of experimental social psychology, 2023)
The cumulative redundancy bias (CRB) refers to people's difficulty in ignoring the redundancy in cumulatively presented information. When people consider which of two competing agents is better, they are influenced by the sequence of events that led to their accumulative total performance. If one agent was ahead most of the time, people consider this agent better - even if the agents are tied eventually. However, we show that an opposite performance-slope bias (PSB) emerges when participants focus on the performance trajectories of agents. When a trailing agent is substantially catching up to the leading agent, people judge the former as the better agent. In four experiments where we manipulated the magnitude of performance slope difference between two agents, we obtained both effects. In Experiments 1 and 2, a large slope difference between agents overshadowed other factors that may have influenced the reversal from CRB to PSB. In Experiments 3 and 4 we showed conclusively with the same design, but for different real-life contexts that the CRB emerges when the slope difference between agents is small while it reverses as the PSB when the slope difference is large. The four experiments demonstrate individuals' ability for flexible cue utilization.